Helpdesk System At PT Himalaya Everest Jaya Jakarta - Wati, Embun Fajar; Maryadi, Dedi (Politeknik Ganesha Medan, 2019)
PT Himalaya Everest Jaya, a company engaged in importers, exporters of electricity and mechanics. In its daily life, PT Himalaya Everest Jaya has used information technology in its operational activities. But problems are often found in supporting operational activities in the field. Where this can hamper the work of every employee who uses it. The problems that often occur include hardware, software, and network connections. Current problem submission is still not effective because employees who have problems must contact the IT directly or by using the telephone. Likewise with recording problems, because the EDP / IT still records every problem using a paper that can be lost or damaged at any time. Therefore, an integrated Helpdesk application is needed and can be accessed quickly by employees and the EDP / IT division. The method used in designing this application is based on the Web, to find out which system is running, the author uses several tools such as Flowmap and UML (Unified Modeling Language), while the system development method uses the Waterfall method. The supporting software used is Xampp, and MySQL as the builder and program documentation. With the existence of a web-based system that has been connected to this database, the process of delivering and handling complaints is expected to be resolved properly and quickly in its handling.